Calibration method for the wavelength and uniformity of pixel response in photodetector arrays (2018)
ABSTRACT: Digital cameras are photodetector arrays that respond to particular bands of the electromagnetic spectrum, and specifically those in the visible spectrum between 380 and 780 nm are the most commonly used. The main cameras function is store the image from an aesthetic point of view, when these are used in home applications. For this rea-son, several processes are used in image reconstruction to improve the visual appearance, even from the manufacturing process of sen-sor decreasing the possibility to obtain optical measurements with this cameras. However, digital cameras can also be used as optical measuring instruments knowing their features in depth. Therefore, in this paper is proposed a calibration method for monochrome digital camera using a monochromator and an automatic rotation system. In this way, the uniformity of the pixels response is verified, bad pixels are detected, and the sensitivity curve is obtained. The results show the advantages of the method to find regions of pixels turned off. Also, the value of sensitivity as a function of wavelength is obtained to verify the regions with significant changes of uniformity. This work aims to the prototyping of a color measurement system and it is very important a comprehensive understanding of the camera.